Strengthening Social Programs to Promote Economic Stability During Childhood. Issue 2 (4th October 2019) - Hardy, Bradley; Hill, Heather D.; Romich, Jennie
Abstract : Economic instability has increased in recent decades and is higher for families with low incomes and Black families. Such instability is thought to be driven primarily by precarious work and unstable family structure. In addition, the social safety net has become less of a stabilizing force for low‐income families, in part because benefits are often tied to employment and earnings. Too much change in economic circumstances may disrupt investments in children, parenting practices, and family routines—particularly if the economic changes are unpredictable, undesired, or not part of upward mobility. Given the considerable evidence that economic circumstances affect child health and development, economic stability can and should be an important goal of multiple policy domains. In this report, we describe economic instability, review the pertinent theories for considering how economic instability might matter to children, and describe ideas for policies that could reduce or moderate instability. We include policies that reduce instability in earnings, use public assistance to stabilize income or reduce material hardship, or enhance parents' capacity to deal with or avoid instability.